Cross-Sector Analysis of Human Resource Recruitment, Selection, and Placement: A Multi-Site Study in Industrial and Higher Education Organizations - Desi Sintyasari; Hendra Yanuar; Mita Sumayyah; Mutiara Syalasy Sumasta; Cindy Rahma Wati; Natasha Ashari; Veronika Putri; Iqbal Maulana; Nauli Ricardo Sitorus; Rahmi Lubis (Journal of General Education and Humanities, 2026)
Human resource procurement, encompassing recruitment, selection, and placement, plays a strategic role in ensuring organizational effectiveness. However, these practices vary across organizations due to differences in operational objectives, organizational characteristics, and competency requirements. This study aims to analyze and compare human resource recruitment, selection, and placement practices in three organizations representing the manufacturing, plantation, and higher education sectors. A qualitative multi-site research design was employed involving PT. GA, PT. TS, and the “SD” Higher Education Foundation. Data were collected through observations, semi-structured interviews with 15 informants, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that each organization implements contextual human resource procurement strategies. PT. GA emphasizes technical competence and operational efficiency, PT. TS prioritizes physical readiness, fieldwork experience, and adaptability, while the “SD” Higher Education Foundation focuses on academic competence, professionalism, and educational quality through competency-based recruitment, selection, and placement. The study also identifies challenges related to competency mismatch, recommendation-based recruitment bias, workforce turnover, and the limited utilization of digital human resource management systems. This study contributes to the human resource management literature by providing a cross-sector perspective that demonstrates how organizational context shapes recruitment, selection, and placement practices. The findings also offer practical implications for developing competency-based and adaptive human resource management systems across different organizational settings.